Geo-authentic Tibetan medicine: a traditional pharmacological resource for promoting human health and wellness - Wang, Ning; Zhu, Hongkang (Frontiers in Pharmacology, 2024)
Traditional Tibetan medicine (TTM) is an ancient healing system, which has been practiced for more than 2000 years, involving the use of various medicinal plants to prevent and treat acute mountain sickness, depression, asthma etc. Geo-authentic medicinal materials, also known as "Daodi herbs" in Chinese, demonstrate the heightened efficacy and quality relative to their counterparts sourced from alternative geographic locales. In 2024, eight medicinal materials, typified by Cordyceps sinensis Sacc., were listed as geo-authentic Tibetan medicine under administration of the local government. However, there is no comprehensive review on these geo-authentic TTMs, especial focused on their pharmacological benefits to human health. This review aims to document the pharmacological properties, phytochemical components, safety and toxicity, and future developments of the geo-authentic TTMs, which played the essential role in promoting health and well-being. Plant-derivatives molecules (ie., polysaccharides, flavonoids, glycosides, terpenoids, alkaloids) in TTMs showed therapeutic 2 / 50 potential for the management of both mental and physical health. Finally, the applications and prospects of TTMs plants are forecast, which may lend support to the use of species of this family in folk medicine for human wellness and open up new way to promote public health in modern societies.